(untitled) (Geologica Macedonica, 2022)
Within this paper is presented information about current study of radon and radium analysis in self-bottled drinking water from the public water fountain “Elixir” in the Moklište area, city of Kavadarci. Obtained results for the radon in water measurements, for the preventive method taken samples, ranged from 3.40 up to 3.69 Bq·l–1, while values for the typical method taken samples ranged from 2.60 up to 3.62 Bq·l–1. Radon concentration measured from samples obtained in typical way showed lower than the corresponding values obtained using the preventive sampling method, where comparison of respective samples P1-T1, P2-T2 and P3-T3 have shown lower values of 1.09 %, 17.62 % and 23.53 % for typical method. Obtained results for the radium in water, for the preventive method taken samples, ranged from 0.08 up to 0.19 Bq·l–1 while values for the typical method taken samples ranged from 0.11 up to 0.14 Bq·l -1. Radium concentration measured from samples obtained in typical way showed lower than the corresponding values obtained using the preventive sampling method, where comparison of respective samples P1- T1, P2-T2 and P3-T3 have shown differences in respective values of of 8.33 %, 42.11 % and 42.86 % for typical method. The committed effective dose for the population consuming the self-bottled water from the Moklište public drinking water fountain of the region was estimated using the concentration of 222Rn and 226Ra in water samples, which ranges from 21.09 to 33.43 Sv y–1 for preventive method and from 22.79 to 26.01 Sv y–1 for traditional method.